1987
DOI: 10.1093/jn/117.6.1154
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sodium Intake Does Not Affect Postprandial Sodium Concentrations in Human Milk

Abstract: Sodium concentration in human milk is known to vary diurnally and throughout lactation. To investigate potential postprandial variation, eight exclusively breast-feeding mothers of infants 10-19 wk of age were visited on two different days after a 3-h fast. On one day, they were fed a low sodium lunch (130 mg), and on the other, the same lunch with a high sodium content (2175 mg). Milk samples were collected before each lunch and breasts were emptied with an electric pump. After lunch, samples were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…11 We did not observe a significant difference in d7 milk Na:K according to mastitis status at d14, or non-mastitis infections reported at either d7 or d14 (data not shown), thus only the single case of mastitis on d7 was excluded from our analyses. 13 It has been demonstrated that milk Na markedly declines as the mammary gland progresses toward mature milk production. 3 We analyzed milk sodium as a ratio to potassium because this approach adjusts for variation in the lipid-free purity of the aqueous fraction of the milk sample and thus produces less error in assessing its relation to mammary gland tight junction formation.…”
Section: Discussionmentioning
confidence: 99%
“…11 We did not observe a significant difference in d7 milk Na:K according to mastitis status at d14, or non-mastitis infections reported at either d7 or d14 (data not shown), thus only the single case of mastitis on d7 was excluded from our analyses. 13 It has been demonstrated that milk Na markedly declines as the mammary gland progresses toward mature milk production. 3 We analyzed milk sodium as a ratio to potassium because this approach adjusts for variation in the lipid-free purity of the aqueous fraction of the milk sample and thus produces less error in assessing its relation to mammary gland tight junction formation.…”
Section: Discussionmentioning
confidence: 99%
“…44 Dietary potassium may influence milk potassium more significantly. Maternal sodium or potassium intake has no immediate influence, either high or low, on postprandial milk sodium or potassium concentrations.…”
Section: Sodium Potassium and Chlorinementioning
confidence: 99%
“…No presente estudo, as médias de sódio no colostro de 48 horas das nutrizes normotensas e hipertensas foram superiores aos valores relatados por Neville et al 21 e Grumash et al 4 , não havendo distinção entre aquelas de nutrizes normotensas e hipertensas. Ereman et al 22 afirmaram que, dos minerais no leite humano, a concentração de sódio é a mais variável durante toda a lactação, e Wack et al 23 relataram existir variações intra e inter-indivíduos quanto à secreção deste eletrólito no leite humano. A existência dessas variações inter e intra-individuais na composição do leite humano poderiam justificar, em parte, as diferenças encontradas entre as concentrações de sódio do presente estudo e os dados da literatura.…”
Section: Internaçãounclassified